Pengaruh Jalur Pelaporan dan Komitmen Religius terhadap Niat Melakukan Whistleblowing: Sebuah Studi Eksperimen - Heri Faisal Harahap; Fauzan Misra; Firdaus Firdaus (Jurnal Ilmiah Akuntansi, 2020)
Whistleblowing is considered as one of the effective ways in preventing and detecting fraud. This study aims to examine the effect of reporting channels and religius commitment on the whistleblowing intention. To achieve this goal, study participants acted as company staff in a case of fraud. This study uses a 2x2 between-subject design which involved 100 participants. As predicted, the results of the study showed that individual's intention to whistleblowing was higher on anonymous reporting channels than non-anonymous. However, in contrast to predictions, this study found there is no difference in whistleblowing intention based on the level of religius commitment. This finding implies that the existence of anonim reporting channels may trigger individual to do whistleblowing.